Does tranexamic acid improve intra-operative visualisation in endoscopic ear surgery? A double-blind, randomised, controlled trial. Issue 12 (13th December 2019) - Das, A; Mitra, S; Ghosh, D; Kumar, S; Sengupta, A
Abstract: Objective: To assess the effect of tranexamic acid on intra-operative bleeding and surgical field visualisation. Methods: Fifty patients undergoing various endoscopic ear surgical procedures, including endoscopic tympanoplasty, endoscopic atticotomy or mastoidectomy, endoscopic ossiculoplasty, and endoscopic stapedotomy, were randomly assigned to: a study group that received tranexamic acid or a control group which received normal saline. The intra-operative bleeding and operative field visualisation was graded using the Das and Mitra endoscopic ear surgery bleeding and field visibility score, which was separately analysed for the external auditory canal and the middle ear. Results: The Das and Mitra score was better ( p < 0.05) in the group that received tranexamic acid as a haemostat when working in the external auditory canal; with respect to the middle ear, no statistically significant difference was found between the two agents. Mean values for mean arterial pressure, heart rate and surgical time were comparable in both groups, with no statistically significant differences. Conclusion: Tranexamic acid appears to be an effective haemostat in endoscopic ear surgery, thus improving surgical field visualisation, especially during manipulation of the external auditory canal soft tissues.